Competition for dominance within replicating quasispecies during prolonged SARS-CoV-2 infection in an immunocompromised host. Issue 1 (21st May 2022) - Caccuri, Francesca; Messali, Serena; Bortolotti, Daria; Di Silvestre, Dario; De Palma, Antonella; Cattaneo, Chiara; Bertelli, Anna; Zani, Alberto; Milanesi, Maria; Giovanetti, Marta; Campisi, Giovanni; Gentili, Valentina; et al.
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern (VOCs) emerge for their capability to better adapt to the human host aimed and enhance human-to-human transmission. Mutations in spike largely contributed to adaptation. Viral persistence is a prerequisite for intra-host virus evolution, and this likely occurred in immunocompromised patients who allow intra-host long-term viral replication. The underlying mechanism leading to the emergence of variants during viral persistence in the immunocompromised host is still unknown. Here, we show the existence of an ensemble of minor mutants in the early biological samples obtained from an immunocompromised patient and their dynamic interplay with the master mutant during a persistent and productive long-term infection. In particular, after 222 days of active viral replication, the original master mutant, named MB61 0, was replaced by a minor quasispecies (MB61 222 ) expressing two critical mutations in spike, namely Q493K and N501T. Isolation of the two viruses allowed us to show that MB61 222 entry into target cells occurred mainly by the fusion at the plasma membrane (PM), whereas endocytosis characterized the entry mechanism used by MB61 0 . Interestingly, coinfection of two human cell lines of different origin with the SARS-CoV-2 isolates highlighted the early and dramatic predominance of MB61 222 over MB61 0 replication. This finding may be explained by a faster replicative activity of MB61 222 as compared to MB61 0 as well as by the capability of MB61 222 to induce peculiar viral RNA-sensing mechanisms leading to an increased production of interferons (IFNs) and, in particular, of IFN-induced transmembrane protein 1 (IFITM1) and IFITM2. Indeed, it has been recently shown that IFITM2 is able to restrict SARS-CoV-2 entry occurring by endocytosis. In this regard, MB61 222 may escape the antiviral activity of IFITMs by using the PM fusion pathway for entry into the target cell, whereas MB61 0 cannot escape this host antiviral response during MB61 222 coinfection, since it has endocytosis as the main pathway of entry. Altogether, our data support the evidence of quasispecies fighting for host dominance by taking benefit from the cell machinery to restrict the productive infection of competitors in the viral ensemble. This finding may explain, at least in part, the extraordinary rapid worldwide turnover of VOCs that use the PM fusion pathway to enter into target cells over the original pandemic strain.